1973
DOI: 10.1111/j.1432-1033.1973.tb03190.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yeast Proteinase and Its Inhibitor on the Inactivation of Tryptophan Synthase from Saccharomyces cerevisiae and Neurospora crassa

Abstract: This paper reports the isolation of a proteinase and a proteinase inhibitor from Saccharornyces cerevisiae S288C (a). The purified proteinase catalyzes the hydrolysis of casein a t neutral pH. It inactivates the holo-tryptophan synthase from Neurospora c r a m but does not inactivate the holo-ornithine aminotransferase from pig kidney. This proteinase can be inhibited either by phenylmethanesulfonyI fluoride (a specific inhibitor for serine proteases), the sulfhydryl reagent, p-mercuribenzoate, or the endogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1974
1974
1981
1981

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…7 is linear up to 90% inhibition of protease B and then it approaches 100% inhibition. Tsai et al (32) obtained an IB calibration curve which was linear only up to 60% inhibition. It seems probable that their soluble casein substrate competes more effectively with 'B than does our insoluble azocoll substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 is linear up to 90% inhibition of protease B and then it approaches 100% inhibition. Tsai et al (32) obtained an IB calibration curve which was linear only up to 60% inhibition. It seems probable that their soluble casein substrate competes more effectively with 'B than does our insoluble azocoll substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Schott and Holzer (31) have obtained protease B in pure form and Hasilik and Holzer (9) have confirmed that protease B is capable of activating chitin synthetase. Tsai et al (32) have studied the inactivation of yeast and Neurospora tryptophan synthase by a yeast protease (presumably protease B) and the inhibition of this destruction by an inhibitor (presumably IB). Molano and Gancedo (25) have reported that a yeast protease inactivates yeast fructose 1,6-bisphosphatase and an inhibitor of this inactivation is also present in yeast.…”
Section: Discussionmentioning
confidence: 99%
“…1) which was hardly observed under the low pH conditions [4] can be greatly stimulated by 4 M urea, by incubation with 0.1 M citrate buffer pH 4 or by extensive dialysis. Since such a phenomenon has not been observed with purified protease I, it may be attributed to a protease-inhibitor complex similar to that observed in yeast [5,10]. After heat treatment (90°C, 5 rain) the proteolytic activity of the complex was completely destroyed, while a heat stable material remained in the supernatant that was active in the inhibition of…”
Section: Isolation Of the Protease-inhibitor Complexmentioning
confidence: 87%
“…Recently we have shown that there exists in Neurospora crassa a group of protease inhibitors which preferentially inhibit the proteolytic enzymes from the same organism [4]. The findings of the coexistence of proteases and inhibitors and their specific interactions in microorganisms led us to the postulate, that the interplay of proteases with their cognate inhibitors may play an important role in the regulation of intracellular proteolytic activity [4,5]. With an aim to understanding the mechanism of this control process, efforts were made to isolate and characterize a protease-inhibitor complex from Neurospora.…”
Section: Introductionmentioning
confidence: 99%
“…The assay for proteolytic activity was performed according to Tsai et al (30), using casein-yellow (Calbiochem, San Diego, Calif.) as the substrate. Before assaying for protease activity, the samples were concentrated 10-fold by a Minicon-B 15 (Amicon Corp., Lexington, Mass.).…”
mentioning
confidence: 99%